2021
DOI: 10.1002/pc.26305
|View full text |Cite
|
Sign up to set email alerts
|

A comparative evaluation of chemical, mechanical, and thermal properties of oil palm fiber/pineapple fiber reinforced phenolic hybrid composites

Abstract: In this paper, oil palm fiber (OPF) and pineapple fiber (PALF) reinforced biophenolic resin (BPHR) composites and hybrid composites were fabricated by hand lay-up technique. Structural, thermal and mechanical properties of pure and hybrid composites analyzed by Fourier transform infrared (FTIR), thermal gravimetric analyzer (TGA), dynamic mechanical analyzer (DMA), and universal testing machine. Achieved results indicated that OPF/PALF hybrid composites show better properties as compared with pure composites. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…TGA is a consistent method utilized to investigate the thermal stability and the degradation profile of polymeric materials. [ 40–42 ] The thermal stability is evaluated by TGA in terms of the initial degradation temperature (T i ), the final degradation temperature (T f ), the maximum temperature (From DTG curves), and the residue at the final decomposition temperature. Figure 3 shows a comparison of TGA curves of untreated and treated pure composites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TGA is a consistent method utilized to investigate the thermal stability and the degradation profile of polymeric materials. [ 40–42 ] The thermal stability is evaluated by TGA in terms of the initial degradation temperature (T i ), the final degradation temperature (T f ), the maximum temperature (From DTG curves), and the residue at the final decomposition temperature. Figure 3 shows a comparison of TGA curves of untreated and treated pure composites.…”
Section: Resultsmentioning
confidence: 99%
“…TGA is a consistent method utilized to investigate the thermal stability and the degradation profile of polymeric materials. [40][41][42] The thermal stability is evaluated by TGA in terms of the initial degradation temperature (T i ), F I G U R E 2 FTIR spectra of treated and untreated fiber composites. FTIR, Fourier transform infrared spectroscopy the final degradation temperature (T f ), the maximum temperature (From DTG curves), and the residue at the final decomposition temperature.…”
Section: Thermal Stabilitymentioning
confidence: 99%
“…The addition of FF fiber volume from 10 to 30% improved the σ f of the composite by 44.98%. The composite prepared by Jawaid et al, 2021 [ 60 ], Mohanavel et al, 2021 [ 110 ], Jumaidin et al, 2021 [ 111 ], Devireddy et al, 2021 [ 112 ] and Ajith et al, 2014 [ 113 ], showed comparable flexural strength to that of FF/E composites.…”
Section: Resultsmentioning
confidence: 99%
“…Few natural fibers show mechanical properties comparable with that of glass fibers [ 52 , 53 , 54 , 55 , 56 , 57 ]. The thermomechanical properties of natural composites are being enhanced by developing hybrid composites to suit the requirements of various applications [ 58 , 59 , 60 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from their low cost and light weight, natural fiber reinforced composites are getting more attention because they are renewable, low energy consumption, and biodegradable. Aside from these benefits, increasing environmental concerns and rising petroleum consumption levels are driving the entire world to use more sustainable natural resources such as natural fibers [ 2 , 3 , 4 , 5 ]. Therefore, natural fibers are rising as reinforcing fibers for composite materials in the automotive, furniture, packaging, and construction industries due to these advantages [ 6 ].…”
Section: Introductionmentioning
confidence: 99%